Targeting bacterial biofilms using polymer-stabilized nanoemulsions - Aamir Hassan, Muhammad; Abdelaziz, Maged; Noor, Sadaf; Nangmo Kemda, Pamela; Tan, Ayse; Park, Jungmi; Rotello, Vincent M. (Taylor & Francis Ltd, 2025)
IntroductionAntimicrobial resistance (AMR) in bacterial infections is a critical global health threat, contributing significantly to increased morbidity and mortality. This challenge is further amplified by biofilms that act as a protective barrier around bacteria, limiting the effective action of antibiotics and host immune responses.Areas coveredThis review highlights the potential of nanoemulsion (NE) systems in delivering hydrophobic payloads, particularly essential oils (EOs), into biofilms, negatively charged extracellular polymeric substance (EPS) matrix. While essential oils exhibit strong antimicrobial properties, their effectiveness against biofilms is restricted due to poor bioavailability and limited biofilm penetration.Expert opinionNE systems employing natural, semisynthetic, and synthetic polymeric scaffolds offer an effective delivery method for EOs, enabling enhanced penetration into the negatively charged EPS matrix of biofilms. These therapeutics have significant potential for treating refractory biofilm-related AMR infections.
Keywords: Antimicrobial Resistance; Polymeric Nanoemulsion; Biofilm Penetration; Essential-Oil Bioavailability; Refractory Infections